Ashkharatsuyts (Armenian Geography) of the 5th-7th centuries by Movses Khorenatsi and Anania Shirakatsi. Preface, translation and comments by A. Zh. Belgorod: ZEBRA Publishing House, 2023. 184 p. - A. P. Belikov (Гуманитарные и юридические исследования, 2024)
.